Kinetic study of synthesis reaction of lignosulfonate using isothermal differential scanning calorimetry method - Giang, Nguyen Truong; Kien, Tran Trung; Hoa, Nguyen Thi; Thiem, Pham Van (Vietnam Journal of Science and Technology, 2017)
The kinetics of lignin methylsulfonation were studied in solution by using differential scanning calorimetry (DSC) techniques under an isothermal program, at 55, 65, 75 and 85°C, respectively. It was found that activation energy, Eα =  41.26 kJ/mol, and preexponential factor A was 1.85×103 s-1.